Digital Psychology Classification, Fields of Work and Research - Metz, Maren; Spies, Birgit (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer, 2023)
This Essential provides an initial overview of the intersections of digitalisation and psychology and outlines the developing field of digital psychology. It highlights current projects, formulates research questions and aims to stimulate discussion, action and further development. The content - Psychology and the Digital - Development of psychology with regard to digitalisation - Location of digital psychology - Development and use of digital technologies in psychology - Future and development of digital psychology Target groups - Psychologists, managers, digital leaders, speakers and experts for digital processes, process consultants for digital change processes The authors Maren Metz is head of the Psychology programme at the Department of Health and Care at the HFH - Hamburger Fern-Hochschule. She has experience in science and research in the areas of (virtual) learning and change strategies, especially in the area of e-coaching. Birgit Spies holds the professorship for education and digitalisation at the Fresenius University of Applied Sciences and heads the distance learning programme Media and Communication Management (B.A.). Her work and research focuses in particular on teaching and learning with digital media and education. This book is a translation of an original German edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.
Introduction -- Psychology and the digital -- State of development and research -- Outlook: Future and development of digital psychology.
Keywords: Psychology, Industrial; Supervision; Psychological consultation; Work and Organizational Psychology; Supervision; Consulting